Impact of combined medial and lateral bone marrow lesions on clinical outcomes after medial unicompartmental knee arthroplasty - Guanglei Cao; Anhong Wang; Qing Liu; Jian Liu; Yuan Liu; Ye Huang (The Bone & Joint Journal, 2026)
Aims Although the influence of medial bone marrow lesions (BMLs) on outcomes after medial unicompartmental knee arthroplasty (UKA) has been studied, the impact of concomitant lateral compartmental BMLs remains unclear. This study aims to determine whether the lateral BMLs, in addition to medial BMLs, influence clinical outcomes in patients undergoing medial UKA. Methods We retrospectively reviewed patients who underwent medial UKA between January 2016 and December 2019 and had preoperative MRI. A total of 86 patients with isolated medial BMLs (BML-M) and 38 with combined medial and lateral BMLs (BML-M+L) were included. Clinical outcomes were assessed using the Numeric Rating Scale (NRS) and Oxford Knee Score (OKS). Radiological evaluation included pathological radiolucent lines, osteoarthritis progression in the lateral compartment, mechanical femorotibial angle (mFTA), and postoperative alignment zones. The proportion of patients achieving the minimal clinically important difference (MCID) for each score and a well-aligned mechanical axis was also calculated. Multivariable linear regression was employed to determine whether concomitant lateral BMLs independently influenced OKS improvement. Results The mean follow-up was 6.4 years (SD 1.1). Both groups demonstrated significant improvements from baseline in NRS and OKS (both p < 0.001). No significant differences were found in preoperative and postoperative mFTA between the two groups. No pathological radiolucent lines were detected in either group and no significant difference was found in the radiological progression of the lateral compartment between the BML-M group and the BML-M+L group (12.8% (n = 11) vs 13.1% (n = 5); p = 0.550). There were no between-group differences in either preoperative or postoperative scores, or in the proportion of patients reaching the MCID for NRS or OKS, or in the patients attaining a well-aligned mechanical axis. In the multivariable model, combined medial and lateral compartmental BMLs were not independently associated with OKS improvement ( β = 0.548 (95% CI -3.400 to 4.490); p = 0.784). Conclusion In MRI-selected medial UKA patients with medial BMLs, mild concomitant lateral BMLs, in the absence of severe lateral cartilage wear and lateral meniscal extrusion, were not associated with inferior mid-term patient-reported outcomes or alignment. Cite this article: Bone Joint J 2026;108-B(9):1121–1128.